2021
DOI: 10.21203/rs.3.rs-617108/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RAPIDIRON: Reducing Anaemia in Pregnancy in India A 3-Arm, Randomized-Controlled Trial Comparing The Effectiveness of Oral Iron With Single-Dose Intravenous Iron In The Treatment of Iron Deficiency Anaemia In Pregnant Women And Reducing Low Birth Weight Deliveries.

Abstract: Background: Anaemia is a worldwide problem and iron deficiency is the most common cause. In pregnancy, anaemia increases the risk of adverse maternal, foetal and neonatal outcomes.India’s anaemia rate is among the highest in the world with India’s National Family Health Survey indicating over 50% of pregnant women were affected by anaemia. India’s Anaemia Mukt Bharat-Intensified National Iron Plus Initiative aims to reduce the prevalence of anaemia among reproductive-age women, adolescents and children by 3% p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…We found the weight percentiles by GW could be used to estimate the risk of full-term LBW or macrosomia (OBW) during pregnancy, both LBW and macrosomia were prevalent and associated with increased risks of perinatal morbidity and mortality [24][25][26][27][28].This study showed more frequency of maternal weight under 10th percentile during pregnancy was higher risk of LBW and lower risk of OBW, in contrast more frequency of maternal weight over 90th percentile during pregnancy was lower risk of LBW and higher risk of OBW, but we didn't nd similar report. Many previous reported that inappropriate amount or rate of GWG were associated with adverse pregnancy outcomes including LBW and macrosomia [2,29,30], and low or excess pre-pregnancy BMI, gestational diabetes mellitus, and maternal anemia also increased the risk of LBW or macrosomia [31][32][33][34][35][36][37], this paper also showed these factors were associated with LBW or OBW. Furthermore, maternal age, abnormal reproductive history, assisted reproductive, scarred uterus, parity, delivery mode, and infant sex were considered determinant factors of LBW or OBW, which were consistent with the previous reports [38 -42].…”
Section: Discussionmentioning
confidence: 54%
“…We found the weight percentiles by GW could be used to estimate the risk of full-term LBW or macrosomia (OBW) during pregnancy, both LBW and macrosomia were prevalent and associated with increased risks of perinatal morbidity and mortality [24][25][26][27][28].This study showed more frequency of maternal weight under 10th percentile during pregnancy was higher risk of LBW and lower risk of OBW, in contrast more frequency of maternal weight over 90th percentile during pregnancy was lower risk of LBW and higher risk of OBW, but we didn't nd similar report. Many previous reported that inappropriate amount or rate of GWG were associated with adverse pregnancy outcomes including LBW and macrosomia [2,29,30], and low or excess pre-pregnancy BMI, gestational diabetes mellitus, and maternal anemia also increased the risk of LBW or macrosomia [31][32][33][34][35][36][37], this paper also showed these factors were associated with LBW or OBW. Furthermore, maternal age, abnormal reproductive history, assisted reproductive, scarred uterus, parity, delivery mode, and infant sex were considered determinant factors of LBW or OBW, which were consistent with the previous reports [38 -42].…”
Section: Discussionmentioning
confidence: 54%